Cobalt Diselenide@Reduced graphene oxide based nanohybrid for supercapacitor applications. (1st October 2019) - Song, Yuanqiang; Ran, Ao; Peng, Ziru; Huang, Wutong; Huang, Binglan; Jian, Xian; Mu, Chunhong
Abstract: Cobalt selenide@reduced graphene oxide (CoSe2 @rGO) nanohybrid was successfully synthesized by a facile one-pot hydrothermal method and the electrochemical performance of the nanohybrid was evaluated for supercapacitor applications. The CoSe2 @rGO nanohybrid show superior electrochemical performance in terms of the specific capacitance (449 F g −1  at 2 mV s −1, 219 F g −1  at 0.5 A g −1 ) and enhanced cyclic stability (91.3% capacitance retention for 5000 cycles) relative to pure CoSe2 (196 F g −1  at 2 mV s −1, 99 F g −1  at 0.5 A g −1 ). Such a highly improved specific capacitance found in the CoSe2 @rGO nanohybrid electrode is mainly attributed to the nanosized CoSe2 grains with perfect redox property, more electro-active sites induced by synergetic effect at the interface of CoSe2 and rGO, and high specific area of rGO nanosheets. Besides, with the combination of rGO, the electrical conductivity of the CoSe2 @rGO nanohybrid is highly enhanced, the ion/electron diffusion path is also reduced leading to faster charge transport during charging/discharging process with an improved cyclic stability.